The Theory of Fairness with Integrity in Indonesia’s Electoral Justice System - Raden, Sahran (Fiat Justisia: Jurnal Ilmu Hukum, 2024)
This paper describes the concept of a fairness theory of justice with integrity applied in elections in Indonesia, drawing on the transformation of John Rawls' fairness theory. This theory is employed to examine various components of the electoral legal framework, focusing on the technical implementation of elections and the resolution of electoral disputes to achieve electoral justice in Indonesia. The research utilizes normative legal methodology, characterized by dogmatic legal analysis and theoretical-rational reasoning, employing a logical-deductive approach. It constructs the facts of electoral justice through an extensive review of legal literature and relevant data sources concerning the electoral process in Indonesia. The study addresses electoral practices as instruments of popular sovereignty, highlighting dissatisfaction among stakeholders regarding the election process. The theoretical variables associated with fairness with integrity are critically analyzed for their applicability in fostering electoral justice in Indonesia, emphasizing that a fundamental aim of electoral law enforcement is to ensure the realization of electoral justice.